(untitled) (Global Journal of Human-Social Science, 2015)
This study analysed foregrounding in Festus Iyayi’s three novels: Violence, Heroes, and The Contract. The aim of the study was to discover the function of foregrounding in African literature. A number of passages were extracted from the three novels, beginning with Violence followed by Heroes, and The Contract. These extracts from the three novels were passages that contained foregrounding which revealed the ideological basis of these novels. Images and symbols that projected violence, death, destruction, exploitation, oppression, deprivation, class struggle, etc as well as the plight of the poor revealed Marxism as the ideology that underpinned the three novels. Among the findings are: foregrounding in Iyayi’s novels depicts class struggle; the primary purpose of foregrounding in Iyayi’s novels is not for aesthetic effect; it portrays the less privileged characters as victims of their society; and it contributes to the success of the three novels studied.